Damage detection in structural element through propagating waves using radially weighted and factored RMS. (September 2015) - Jothi Saravanan, T.; Gopalakrishnan, N.; Prasad Rao, N.
Highlights: An explicit approach in SLDV experimentation. A strategy to improve fast spatial visualization of damage. An algorithm to diminish the effect of the source excitation. Abstract: The paper presents an explicit damage visualization methodology in an aluminum plate through the application of wave propagation mechanics. The present work describes a series of experiments and a special signal processing technique, for speedy spatial visualization of damage in different sets of test specimens. Experiments on three aluminum specimens with lead zirconate titanate (PZT)-wave generator is described. Damages are simulated in the form of (1) attached mass, (2) missing bolts and altered boundary conditions and (3) drilled holes with different diameters, simulating both mass and stiffness reduction. Normal responses (out of plane flexure response) are measured with the Scanning Laser Doppler Vibrometer (SLDV). The time signals recorded during measurement have been utilized to calculate the values of Root Mean Square (RMS) response. To compensate for loss of amplitude, due to radially propagating and attenuating wave signal, time samples are weighted by a factor, termed as weighted RMS function. The novelty of the work is the development of an algorithm to compute and plot the RMS of the time function, weighted with the radial distance from the source of excitation and also factored which is termed as Radially Weighted and Factored_RMS (RWF_RMS). Hence the reflected wave from the damage is magnified and the effect of excitation source is diminished. This algorithm has been successfully implemented and tested with the experimental data and the damage location is isolated. The resolution of the technique is evaluated by expressing the size of defect as a fraction of the wavelength. Absolute Maximum Response (AMR), and contour maps for elegant damage detection are attempted. It is anticipated that the suggested approach enables fast and accurate identification of damage location.